Model Kepemimpinan Profetik KH. Ahmad Dahlan dalam Pendidikan Islam - Pamungkas, Oktri; Diarsi, Shifa; Supandi, Muhammad (Lembaga Yasin AlSys, 2021)
Ahmad Dahlan is one of the figures who brought changes in Islamic education to a better direction. Of course, this success cannot be separated from his leadership model which makes the Prophet Muhammad his role model in becoming a leader. He internalizes prophetic leadership in his thoughts and actions. Prophetic leadership is a leadership paradigm that refers to the concept of leadership of the prophets. This study uses a literature review method to discuss the idea of prophetic leadership in terms of humanization, liberation, and transcendence of the KH figure. Ahmad Dahlan in Islamic Education.